Influence of Technologies on Quality of Distance Learning A. Targamadzė, - Targamadzė, A.; Petrauskienė, R.; Rubliauskas, D. (Elektronika ir Elektrotechnika, 2010)
The paper presents a review on modern conceptions of the quality of education and reveals their variety. However, a certain indeterminacy of the definitions of quality can be noticed in their application in the process of learning as the process is under constant changing, it can be affected by different factors. The quality of distance learning is defined as an objective which should be improved during its supply. The paper also touches upon the dependency of the quality of distance learning on the influencing factors, and proposes an algorithm of the process of assurance of the distance learning quality under changes. The purpose of this algorithm is to correct the factors of the process of learning in case requirements or conditions change during the process: we have to analyse which changes (of the content, method, tools and communication) will permit us to obtain the quality of learning that is no lower than the present.